2003
DOI: 10.1103/physreve.68.026218
|View full text |Cite
|
Sign up to set email alerts
|

Boundary effects in the stepwise structure of the Lyapunov spectra for quasi-one-dimensional systems

Abstract: Boundary effects in the stepwise structure of the Lyapunov spectra and corresponding wavelike structure of the Lyapunov vectors are discussed numerically in quasi-one-dimensional systems of many hard disks. Four different types of boundary conditions are constructed by combinations of periodic boundary conditions and hard-wall boundary conditions, and each leads to different stepwise structures of the Lyapunov spectra. We show that for some Lyapunov exponents in the step region, the spatial y component of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
159
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(171 citation statements)
references
References 27 publications
12
159
0
Order By: Relevance
“…In these systems, the value of W (n) usually increases with the Lyapunov index n, and this implies that Lyapunov vectors for the largest exponent region are the most localized. The quantity W (n) has a minimum value of 2, as a minimum of two particles are involved in each collision, and it has been shown numerically that the value of W (n) for the largest Lyapunov exponent approaches 2 as the density approaches zero [23]. It was also shown that W (n) can detect not only the localized behavior of Lyapunov vectors, but also the de-localized behavior observed in the Lyapunov modes [23].…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…In these systems, the value of W (n) usually increases with the Lyapunov index n, and this implies that Lyapunov vectors for the largest exponent region are the most localized. The quantity W (n) has a minimum value of 2, as a minimum of two particles are involved in each collision, and it has been shown numerically that the value of W (n) for the largest Lyapunov exponent approaches 2 as the density approaches zero [23]. It was also shown that W (n) can detect not only the localized behavior of Lyapunov vectors, but also the de-localized behavior observed in the Lyapunov modes [23].…”
mentioning
confidence: 92%
“…One of the most significant points of the Lyapunov spectrum is that each Lyapunov exponent indicates a time scale given by the inverse of the Lyapunov exponent so we can consider the Lyapunov spectrum as a spectrum of time-scales. The smallest positive Lyapunov exponent region of the spectrum is dominated by macroscopic time and length scale behavior, and here some delocalized mode-like structures (the Lyapunov modes) have been observed in the Lyapunov vectors [5,6,7,8,9,10,11,12,13,14]. On the other hand, the largest Lyapunov exponent region of Lyapunov spectrum is dominated by short time scale behavior, and in this region the Lyapunov vectors are localized (Lyapunov localization).…”
mentioning
confidence: 99%
See 3 more Smart Citations